Nondisclosure as a Contract Remedy: Explaining the Advance-Notice Puzzle - Addison, John T.; Chilton, John B. (Journal of Labor Economics, 1997)
Prior theoretical work predicts an underprovision of advance-notice contracts stemming from their enforcement costs. In the present model, it is rather the fundamental inability of workers to alienate their right to quit taken in conjunction with parameters central to job separation decisions that jointly determine the mix of notice and no-notice contracts observed in equilibrium. Not all equilibrium contracts are efficient, but there is no underprovision of notice. Mandating notice cannot improve on joint value and indeed may reduce it. Furthermore, although a mandate can be merely redistributive, there are cases in which it harms all parties.